TEACHERS' COMPETENCE IN A READING TEST CONSTRUCTION - LUTHFIYATUN THOYYIBAH, - (2018)
Being testing reading literate is one of the requirements to be a professional teacher. It also has been renewed interest and emphasis on language literacy, especially in reading skill. The purposes of this study are to investigate the process of constructing reading tests by the teachers of English at vocational school as well as examine the quality of the teachers' reading tests which reflect their competence in constructing a reading test. This study is a case study design focusing on individual case and involving three teachers of English teaching at three different vocational schools. This study used interview to see the process of reading test construction and utilized the combined criteria from experts as the instrument to examine the quality of the teachers' made tests. Based on the analysis, the study found that the process of constructing reading tests done by the teachers involved finding the basic competence of the materials, choosing the right text, determining the type of questions, deciding on how many numbers in the reading test, and making the scoring. In regard to the quality of the teachers' made reading tests, the results from the rating scales showed that the first teachers' reading tests were considered poor and good as the tests achieved rating score 69 and 87 respectively. The second teacher's reading tests were considered very poor since the tests' scores were 51 and 56. The third teacher's reading test, however, was considered as good since it scores 81. This implies that while the two teachers may probably have sufficient knowledge in constructing the reading test in terms of test planning, relevance, balance, efficiency, validity, reliability, adequacy of test items, and the technical sound of the reading test, the other teacher's competence in constructing the test was not fully developed. It is recommended for the teacher of English to use authentic text for reading test. It also suggested to create high level of comprehension questions based on the authentic text. For further research, it will be better to use a more complete checklist as one of the instruments used in the study and involving more participants.